Molecular identification of Streptococcus sp. and antibiotic resistance genes present in Tilapia farms (Oreochromis niloticus) from the Northern Pacific region, Costa Rica - Karen Oviedo-Bolaños (2021)
Streptococcosis is a bacterial disease in tilapia that produces economic losses, caused mainly by Streptococcus agalactiae and S. iniae. It is treated using oxytetracycline and florfenicol, which when inappropriately used promotes the selection of antibiotic resistance genes (ARGs). The disease has been mainly associated with stress events such as variations in temperature. The aims of the present study were (1) to detect by molecular methods two species of Streptococcus sp. in a tilapia farm, (2) to relate their presence to physicochemical parameters in the culture system, and (3) to detect the presence of ARGs in tilapia tissues and/or ponds. Tilapia grow-out ponds (n = 30) were sampled, collecting 15 individuals per pond. The physicochemical parameters of water were measured in each pond. Per pond, organs such as the liver, spleen, brain, and eyes were collected from each individual. Then, each organ type was pooled with the respective organ of the other individuals, processed for DNA extraction, and used for PCR analyses to determine the presence of S. agalactiae and S. iniae and for the detection of ARGs (tetM, tetO, fexA, and ermB). The correlations between the presence of S. agalactiae and water physicochemical parameters were determined. Sixty percent of the ponds and 46% of the organ pools were positive for S. agalactiae, whereas S. iniae was not detected. The positive samples showed the following resistance genes: tet(O) (29.1%), tet(M) (12.7%), and erm(B) (1.8%). A moderate but significant positive correlation was found between temperature and the presence of S. agalactiae. This work reported the molecular detection of two species of Streptococcus and ARGs, providing information that allows fast and effective control of these pathogens in tilapia farming. In addition, a future complementary study on Streptococcus sp. serotype distribution and antibiotic resistance genes from tilapia cultured in Costa Rica could also contribute to increase the knowledge of S. agalactiae infections in tilapia farming worldwide.